Computer game of UNO / Zety Marlia Zainal Abidin - Zety Marlia , Zainal Abidin (2004)
Computer Game of UNO is an interactive computer card game package that provides distinction capabilities from the class is card game. From a manual to digital application, still Computer Game of UNO applies the basic rule of the game. The usage of the system is suitable for all the range of age, and illiterate computer users for a starting practical. This simplicity and less time consuming game is a one-to-one system where only one user interact with minimum one or maximum three computer players. There are several main fu nctions such as system detecting the input from user and sound manipu lation for call "UNO". The login and logout session for user to register their nickname and to exit from game also been provided to case user. Computer Game of UNO is easily lo deliver because it requires less installation process and quick response time for a display, plus the control keys using mouse most of the time make user able to play the game at ease. Considering computer game is widely used by human from all walks of life, the sense of entertaining and challenging would not be separated in order to give satisfaction and as an exercise the skill in card game.